2019
DOI: 10.1177/1010428319863627
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of Osteopontin (SPP1) in colorectal carcinoma requires a personalized molecular approach

Abstract: Stratification of colorectal cancer for better management and tangible clinical outcomes is lacking in clinical practice. To reach this goal, the identification of reliable biomarker(s) is a prerequisite to deliver personalized colorectal cancer theranostics. Osteopontin (SPP1) is a key extracellular matrix protein involved in several pathophysiological processes including cancer progression and metastasis. However, the exact molecular mechanisms regulating its expression, localization, and molecular functions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 49 publications
1
20
0
Order By: Relevance
“…Osteopontin (OPN) is widely distributed in various tissues and cells and is involved in tissue repair, self-metabolism, and other functions that allow OPN to play an important role in tumor metastasis [4446]. Presently, it has been shown that OPN is related to both the EMT and MET processes of tumor cells.…”
Section: Cxcl8 and Its Receptors In The Process Of Met And Colonizmentioning
confidence: 99%
“…Osteopontin (OPN) is widely distributed in various tissues and cells and is involved in tissue repair, self-metabolism, and other functions that allow OPN to play an important role in tumor metastasis [4446]. Presently, it has been shown that OPN is related to both the EMT and MET processes of tumor cells.…”
Section: Cxcl8 and Its Receptors In The Process Of Met And Colonizmentioning
confidence: 99%
“…In multiple malignant tumors such as gastric, esophageal, and colorectal cancers, SPP1 could be detected to have a significantly high expression. Moreover, the SPP1 expression level was significantly higher in tumors with higher malignancy than that in tumors with lower malignancy (Lin et al, 2015;Xu et al, 2017;Chen et al, 2018;Assidi et al, 2019). Xu et al (2017) found that SPP1 could activate the epithelial-mesenchymal transition (EMT) pathway to promote the metastasis of colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In the immune-risk model, secreted phosphoprotein 1 (SPP1 or OPN) is a widely studied signature in tumors, which is normally involved in the process of osteoclasts' attachment to mineralized bone matrix. It is elevated in tumors for progression and metastasis, and its alternatively spliced variants are related to many malignant traits in cancers, such as epithelial-mesenchymal plasticity, cancer cell stemness, chemoresistance, and radioresistance [15][16][17][18][19][20]. However, the variants of SPP1 due to aberrantly processing may cause autoimmune reactions in tumors, which can lead to better outcomes in partial patients [21,22].…”
Section: Discussionmentioning
confidence: 99%